Obesity and other Modifiable Cardiometabolic Risk Factors in Adolescents in Lagos, Nigeria - Salisu-Olatunji, S. O.; Odugbemi, Babatunde; Adejumo, O. A.; Mohammed, A. S.; Alakija, W (The Nigerian Health Journal, 2024)
Background: The true burden of non-communicable diseases and their risk factors among adolescents in developing countries is unknown. The objective was to assess the prevalence of obesity and other modifiable cardio-metabolic risk factors among adolescents in Lagos State, Nigeria.Method: A cross-sectional study design was used. Five hundred and six in-school adolescents were recruited through a multistage sampling technique. Data was collected using a questionnaire adapted from the WHO STEPS chronic disease surveillance tool. Anthropometric measurements were also taken. Respondents were classified as having either low or high metabolic risk based on computed risk scores. Logistic regression was used to determine the predictors of high metabolic risk. The level of significance was set at p